Effects of human resource capability, production planning system, technology and organizational culture on SME’s performance in West Java - Nu’man, A. Harits (2017)
This study, in particular, addresses the gap in the effect of Human Resource Capability (HRC), Production Planning System (PPS), Technology (TECH) and Organizational Culture (OC) on the performance of the automotive- and –metal- sectors- based SMEs in West Java. Earlier literature shows that scholars have conducted various studies on these variables individually, but this might not reflect the whole picture. This study investigated the effects of HRC, PPS, Technology, as independent variables, and OC as a mediating variable on Organizational Performance (OP). The theoretical framework of this study used a Resource-based View (RBV) and Dynamic Capabilities (DC). The research instrument consisted of 92 items adapted from previous studies. Out of 370 sets of questionnaires distributed, 360 (97.30%) were usable. The research employed the systematic sampling technique and the AMOS 21 software to draw and make conclusions. The findings support the belief that a specific combination of strategic HRC, PPS and TECH factors improve OP. These results are in line with previous research studies, which agree that HRC, PPS and TECH lead to improved OP. The current findings indicate that RBV and DC lend support in describing the effects of HRC, PPS, TECH and OP, directly or indirectly, through OC. The study suggests important implications for practitioners in building and strengthening the competitive approach of their organizations in the hyper-competitive environment of SMEs. This finding will be useful to government agencies in making new policies to support strategic plans, to increase performance and contribution to GDP which will create jobs, and encourage the development of SMEs to have global competitiveness, as the main targets of the strategic plan of the industry in West Java.